EFEK MEDIASI DARI PENGEMBANGAN KARIR PADA PENGARUH PELATIHAN DAN PENGEMBANGAN TERHADAP KEPUASAN KERJA DI PT PLN (PERSERO) PUSAT - Difa Anggita; Sylvia Diana Purba (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2015)
The purpose of this research is to test the effect mediation of career development on the influence of training and development toward to job satisfaction at PT PLN (PERSERO) Pusat. Data collected using a purposive sampling. There are 80 respondents used as participants. The path analysis is used by analytical tools of Preacher-Hayes the Simple Mediation Model with SPSS 22 for mac with macro and syntax. This research findings that the career development has mediating effect on the influence of training and development toward job satisfaction.